Performance Study of Electrodialysis for Treatment Fuel Washing Wastewater - Abdul Majeed, Basma A.; Zubaidy, Maitham Adham (Iraqi Journal of Chemical and Petroleum Engineering, 2016)
In this work, electrodialysis (ED) has been demonstrated to be appropriate technique for reducing the electrical conductivity of real wastewater from fuel washing unit, which has been previously treated by other electrochemical technology (electrocoagulation and electrooxidation).  A five cell electrodialysis stack, with an active membrane area of 60 cm2 per cell was employed. During a batch recirculation mode ED system, the effects of parameters such as electrical potential applied (6-18 V) and flow rate of streams (0.5-1.7 L/min.) on the performance of the total dissolved solids (TDS) separation and specific power consumption (SPC) were studied. The results indicate that the process of ED under potential (15 V) and flow rate (1.4 L/min) are recommended as operation conditions. The removal of TDS achieved was about 95% throughout (80 min.) time of electrodialysis and (1.72 kWh/m3) of SPC. Moreover, SPC increased with an increase in the applied potential of ED stack, while it was not intensely responsive to the change in the flow rate.